Variations of Copahue Volcano Crater Lake and its Relation with Gas and Ash Emission During 2019-2021 - Carbajal, Fabricio Joaquin (2023)
Copahue volcano is located on the international border between Argentina and Chile. It is monitored by the “OAVV” (SEGEMAR, Argentina) and “OVDAS” (SERNAGEOMIN, Chile). Copahue´s lastest and ongoing eruptive cycle initiated in 2012. During 2019-2021, periodic vapor-gases and ash emissions were emitted through the crater, and the hot, acidic crater-lake (CL) presented a significant area variation, in some cases being completely dried. In this work, a correlation between SO2 emissions and changes in the active crater dynamics for the last 3 years is presented. CL area analysis were carried out between 2018-2021, using 3.7 m of resolution satellite images (http://www.planet.com). Additionally, SO2 emissions were studied through the GEE (Google Earth Engine) web platform and contrasted with average flux data from DOAS equipment. Both satellite and ground-based measurements were correlated for the maximum SO2 emission during 2019-2021. Satellite images and meteorological data were integrated, observing a gradual variation in the CL area for the period, reaching maximum values up to 60000 m2, also observing a seasonal component. During 2020 and 2021 winters, maximum SO2 values (up 14000 t/d or day with DOAS and 0,7 Dobson units with GEE) and ash-clouds heights (1700m acl) were identified together with the disappearance of the CL. In addition, an increase in seismic tremor activity was registered for the same time span.This correlation of events allows us to hypothesize: i) during the colder months, the ambient temperature prevents the defrosting that feeds the shallower hydrothermal system, favoring evaporation and decrease of the CL, and consequently, ii) the CL brine generates a shallow chemical seal, from which gases and ash are emitted when the system reaches critical pressure, consistent with the increase in tremor activity. In summary, the activity of the Copahue CL during the 2019-2021 period suggests a seasonal control for gas and ash emissions.